Outdoor physical activity and its relation with self‐reported health in Japanese children: results from the Toyama birth cohort study. (14th June 2015) - Liu, J.; Sekine, M.; Tatsuse, T.; Fujimura, Y.; Hamanishi, S.; Lu, F.; Zheng, X.
Abstract: Background: Few studies have examined trends in engagement in outdoor physical activity as children grow and whether changes in physical activity at different ages affect children's health. This study determined the preference for and frequency of physical activity among Japanese children from ages 6 to 12 years and investigated the effect of physical activity and of change in physical activity on children's self‐reported health. Methods: Data were from the prospective, longitudinal Toyama Birth Cohort Study, a total of 5238 children were followed at their age of 12 years. Preference for and frequency of outdoor physical activity were from the self‐administered questionnaire. Self‐reported health was from the Japanese version of Dartmouth Primary Care Co‐operative project charts. Results: Reporting liking and participating in outdoor physical activity at both ages 6 and 12 years were associated with higher likelihood of good self‐reported health (Odds ratio 1.24 [95% CI: 1.03–1.50] for liking activity and OR = 1.27[1.08, 1.50] for participating in activity) compared with those who did not like or participate in this at only one or at neither age, after adjustment for lifestyle factors and body pain. The adjusted OR was 1.23 (95% CI: 0.97–1.56) for girls whose preference for liking outdoor physical activity was not changed at both ages compared with those whose preference changed. The OR was 1.47 (95% CI: 1.14–1.89) for boys who persisted in participating in the outdoor physical activity than those who did not persist. Conclusions: There is an association between a persistent expression of liking outdoor physical activity and self‐ reported health.